High‐Efficiency and Tunable Circular‐Polarization Beam Splitting with a Liquid‐Filled All‐Metallic Catenary Meta‐Mirror. Issue 7 (13th June 2019) - Xie, Xin; Pu, Mingbo; Liu, Kaipeng; Ma, Xiaoliang; Li, Xiong; Yang, Jianing; Luo, Xiangang
Abstract: Circular‐polarization beam splitting is one functionality of interest in polarization control. However, current splitters suffer from limitations in either efficiency or tunability. It is theoretically and experimentally demonstrated that a meta‐mirror composed of catenary‐shaped metallic gratings can efficiently deflect left‐handed and right‐handed circularly polarized waves in opposite directions with power efficiency of over 90%. This ultrahigh efficiency is attributed to the nearly perfect polarization conversion and continuous phase profile of the metallic catenary structure. Furthermore, the meta‐mirror demonstrates high beam‐splitting tunability with ethanol injected into the catenary groove. By controlling ethanol depth, the working frequency for peak deflection can be continuously tuned from 10.5 to 8.5 GHz. It is believed that this approach can provide valuable guidance for efficient and dynamic control of electromagnetic waves for various applications. Abstract : A meta‐mirror designed with a catenary‐shaped metallic grating that efficiently deflects left‐handed and right‐handed circularly polarized waves in opposite directions with power efficiency of over 90% is reported. By injecting ethanol into the catenary grooves and controlling the ethanol depth, the working frequency can be continuously tuned from 10.5 to 8.5 GHz.